2005
DOI: 10.1111/j.1365-313x.2005.02539.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐to‐cell movement of Potato Potexvirus X is dependent on suppression of RNA silencing

Abstract: SummaryRNA silencing in transgenic and virus-infected plants involves a mobile silencing signal that can move cell-tocell and systemically through the plant. It is thought that this signal can influence long-distance movement of viruses because protein suppressors of silencing encoded in viral genomes are required for long-distance virus movement. However, until now, it was not known whether the mobile signal could also influence short-range virus movement between cells. Here, through random mutation analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
152
0
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(169 citation statements)
references
References 46 publications
8
152
0
9
Order By: Relevance
“…We introduced amino acid substitutions in the GKS/T motif of the NTPase/RNA helicase domain (Morozov and Solovyev, 2003) to generate TGBp1 AKT . In addition, based on the previously characterized mutation of PVX TGBp1, we constructed three other PlAMV-TGBp1 mutants; TGBp1 E82A is predicted to retain RNA silencing suppressor activity, while TGBp1 P110L and TGBp1 T192A are predicted to have lost the activity (Bayne et al, 2005). Agroinfiltration-mediated transient coexpression assays of GFP and TGBp1 mutants showed that TGBp1 E82A retained RNA silencing suppressor activity whereas TGBp1 AKT and TGBp1 P110L lost it ( Figure 3C).…”
Section: Analyses Of Tgbp1 Mutantsmentioning
confidence: 99%
“…We introduced amino acid substitutions in the GKS/T motif of the NTPase/RNA helicase domain (Morozov and Solovyev, 2003) to generate TGBp1 AKT . In addition, based on the previously characterized mutation of PVX TGBp1, we constructed three other PlAMV-TGBp1 mutants; TGBp1 E82A is predicted to retain RNA silencing suppressor activity, while TGBp1 P110L and TGBp1 T192A are predicted to have lost the activity (Bayne et al, 2005). Agroinfiltration-mediated transient coexpression assays of GFP and TGBp1 mutants showed that TGBp1 E82A retained RNA silencing suppressor activity whereas TGBp1 AKT and TGBp1 P110L lost it ( Figure 3C).…”
Section: Analyses Of Tgbp1 Mutantsmentioning
confidence: 99%
“…4A). PVX encodes three genes required for viral movement, known as the triple gene block (TGB), including P25, which also possesses VSR activity (Voinnet et al, 2000;Bayne et al, 2005). We expressed 12K with a version of PVX that expresses GFP but lacks the TGB (PVX-GFPDTGB), to determine whether the 12K protein could substitute for a lack of P25 as a VSR.…”
Section: The Peprsv 12k Protein Possesses Vsr Activitymentioning
confidence: 99%
“…As an alternative approach, we decided to examine whether the RLBV P4 protein could rescue the cell-to-cell movement of PVX expressing GFP but with an in-frame deletion within the TGB1 gene that prevents PVX cell-to-cell movement (Bayne et al, 2005).…”
Section: Rlbv P4 Complements Movement-defective Pvxmentioning
confidence: 99%